Metabolic Engineering of Yeast for the Production of 3-Hydroxypropionic Acid - Ji, Rong-Yu; Ding, Ying; Shi, Tian-Qiong; Lin, Lu; Huang, He; Gao, Zhen; Ji, Xiao-Jun (Frontiers in Microbiology, 2018)
The beta-hydroxy acid 3-hydroxypropionate (3-HP) is an attractive platform compound that can be used as a precursor for many commercially interesting compounds. In order to reduce the dependence on petroleum and follow sustainable development, 3-HP has been produced biologically from glucose or glycerol. It is reported that 3-HP synthesis pathways can be constructed in microbes such as Escherichia coli, Klebsiella pneumoniae and the yeast Saccharomyce cerevisiae. Among these host strains, yeast is prominent because of its strong acid tolerance which can simplify the fermentation process. Currently, the malonyl-CoA reductase pathway and the β-alanine pathway have been successfully constructed in yeast. This review presents the current developments in 3-HP production using yeast as an industrial host. By combining genome-scale engineering tools, malonyl-CoA biosensors and optimization of downstream fermentation pathways, the production of 3-HP in yeast has the potential to reach or even exceed the yield of chemical production in the future.